HASIL VALIDASI DAN UJI KETERPAHAMAN BUKU PENGAYAAN BIOKIMIA MATERI KARBOHIDRAT TERINTEGRASI KEISLAMAN - Tika Ayudia Hartana; Siti Suryaningsih; Buchori Muslim (UIN AR-RANIRY, 2021)
The State Islamic University of Syarif The State Islamic University of Syarif Hidayatullah Jakarta has a vision to become a world-class university with the excellence of scientific, Islamic and Indonesian integration. The chemistry education study program has implemented it in Islamic integrated learning, but there are not many teaching materials available in the form of Islamic integrated enrichment books in several courses, one of which is the biochemistry course. The purpose of this study is to develop teaching materials in the form of an Islamic integrated biochemical enrichment book, carbohydrate materials that are suitable for use. This study uses the 4STMD (Four Steps Teaching Material Development) method. The stages are the stage of selection, structuring, characterization and reduction. Validation data were obtained from chemical integration experts with Islam and media experts. The number of respondents was 59 students of the 8th semester of 2016 class of chemistry education who have received biochemistry courses and Islamic and science courses. This enrichment book has been through field trials, namely testing the comprehension of the text to the respondents. The results of the research from the validation of Islamic religious experts show that the concept of biochemical and Islamic integration is valid and feasible to use with the high category comprehension test of 83.6% with the concept criteria easy to understand. The results of the feasibility test from media experts were 84.57%. Islamic integrated biochemical enrichment book on carbohydrate material is suitable for use with very good criteria. This book can be used as an integrated biochemical enrichment book for Islam and Indonesia.